Conversion of some soil types, subtypes, and varieties between the Taxonomic Classification System of Soils of the Czech Republic and the World Reference Base for Soil Resources - Jitka Sládková (Soil and Water Research, 2010)
The article illustrates the compatibility of the Czech Republic Taxonomic Soil Classification System validated in the CR with the international World Reference Base for Soil Resources. It utilises the archive data on the soil types, subtypes, and varieties from the General survey of agricultural soils in the Czech Republic and soil profiles from new soil survey on the pilot area of Litoměřice district. It indicates the possibilities of the future refinement of both systems.